Financialisation of housing in London: empirical evidence on housing prices - Vergara Perucich, José Francisco. (MDPI, 2023)
This paper aims to empirically review the process of housing financialisation in London, exploring a time series causal relationship between house prices and financial instruments, using the Granger method and a VAR test. In order to carry out this analysis, we use a vector autoregressive model with a monthly data series that seeks to contribute to exploring this relationship. The results are relevant to the important role that the theory of housing financialisation plays in explaining the crisis of access to secure tenure that can be seen in developed nations. The results also provide an empirical background to pursue this theory more specifically in the context of the vectors that are effectively causal to the financialisation processes that impact everyday life through housing prices. The study is original, given that this type of modelling has not previously been carried out for a major world city such as London, and adds to the findings of similar explorations that have applied other methodologies.
Keywords: Central bank; Financialization; FTSE 100; Vivienda-Precios